An Offshore Solar Irradiance Calculator (OSIC) Applied to Photovoltaic Tracking Systems - Ryan Bugeja; Luciano Mule’ Stagno; Lucas Dexarcis (Energies, 2023)
Offshore photovoltaic installations are the future technology in solar energy since they enable the use of the large amount of maritime space, which is especially important when land space is not available. Various research groups are working to create viable installations. However, there are currently no tools available that an offshore system designer can use to quantify the effect of wave response motion on offshore photovoltaic installations. This research presents a new simulation tool termed the Offshore Solar Irradiance Calculator (OSIC) that is able to quantify this effect. Furthermore, a yearly parametric analysis is presented to show the effects of a characteristic wave equation on different offshore tracking systems; namely, horizontal single-axis tracking, vertical single-axis tracking and dual-axis tracking. Finally, another parametric analysis is presented to show the effects of varying wave amplitudes of oscillations on the incident irradiance received by these tracking systems.